Rheumatic fever: a model of a post-infectious autoimmune disease - Kalil, Jorge (Henry Stewart Talks, 2019)
Autoimmunity in humans, Infectious agents can induce breakage of tolerance to self to trigger & maintain autoimmune disease, Rheumatic Fever & Rheumatic Heart Disease (RHD) as paradigms of post-infectious autoimmune disease, Medical & sociological importance of RHD, Genes involved in susceptibility, T cell mediated autoimmunity, Molecular mimicry, Role of Th1 cells in human autoimmunity, How chemokines can drive disease to different site, Identification of autoimmune vs. anti-infection triggering epitopes, Vaccine development to avoid infections & autoimmune disease